2016
DOI: 10.1002/adma.201600979
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Framework‐Derived Honeycomb‐Like Open Porous Nanostructures as Precious‐Metal‐Free Catalysts for Highly Efficient Oxygen Electroreduction

Abstract: Honeycomb-like porous carbon nanostructures are rationally constructed from a metal-organic framework composite. The unique architecture with uniformly distributed high-density active sites significantly enhances the electrocatalytic performance by increasing the accessible active sites and enhancing mass transport of the gas and electrolyte, rendering the resulting catalyst adequate in reaching the desired catalytic performance afforded by Pt for the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
204
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(212 citation statements)
references
References 59 publications
8
204
0
Order By: Relevance
“…The exact content of N in cal-CoZIF-VXC72 determined by element analysis was approximately 0.44 wt%. [3][4][5][6][7][8] However, according to our XPS results, only peaks of C and O were clearly observed, and no other effective doping could be inferred in the cal-CoZIF (Figure 3a,b; Figure S7, Supporting Information). From the TEM images ( Figure S5b After calcination, the XRD peaks of ZIF-67 disappeared, and only a small peak ((311) facets) of Co 3 O 4 (JCPDS card number: 65-3103) was observed.…”
Section: Carbon Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…The exact content of N in cal-CoZIF-VXC72 determined by element analysis was approximately 0.44 wt%. [3][4][5][6][7][8] However, according to our XPS results, only peaks of C and O were clearly observed, and no other effective doping could be inferred in the cal-CoZIF (Figure 3a,b; Figure S7, Supporting Information). From the TEM images ( Figure S5b After calcination, the XRD peaks of ZIF-67 disappeared, and only a small peak ((311) facets) of Co 3 O 4 (JCPDS card number: 65-3103) was observed.…”
Section: Carbon Materialsmentioning
confidence: 97%
“…The pyrolysis of such materials could also contribute to good electrochemical activities. Recently, MOF derivatives have been widely researched in the oxygen reduction reaction (ORR) in alkali solutions [3][4][5][6][7][8] to benefit the hydroxide exchange membrane fuel cell (HEMFC), which is a promising alternative technology to the proton exchange membrane fuel cell due to the virtue of cheap and stable platinum-group-metal-free ORR catalysts. Carbon black is a cheap industrial product that has versatile functions as an additive in plastics, rubbers, pigments, cables, and cells because of its structures and conductivities.…”
mentioning
confidence: 99%
“…In another study, Zhu et al reported the synthesis of N and S dual-doped honeycomb-like porous carbons with Co 9 S 8 NPs (denoted Co 9 S 8 @CNST; where T is the pyrolysis temperature), in which MIL-101-NH 2 was employed as the MOF framework, and thiourea and CoCl 2 were introduced as secondary precursors in the MOF via a chemical impregnation approach. [99] …”
Section: Transition Metal Compounds Compositionmentioning
confidence: 99%
“…[97] Another applicable approach for incorporating transition metal compounds into MOF-derived composites involves the chemical decoration of MOF-derived porous carbons, in which target chemicals are implanted in the MOF precursors or MOFderived carbon substrates by an impregnation method. [48,99] This strategy can not only make full use of the electrochemical properties of integrated active compounds, but also exploits the unique characteristics of MOF-derived carbons, including high surface area, uniform porosity, good conductivity, and welldefined structure. For example, Liu et al prepared a MoS 2 -based 3D nanoporous composite (MoS 2 /3D-NPC).…”
Section: Transition Metal Compounds Compositionmentioning
confidence: 99%
See 1 more Smart Citation